Are Demographics Adequate Controls for Cell-Phone-Only Coverage Bias in Mass Communication Research?. (September 2015) - Watson, Brendan R.; Zamith, Rodrigo; Cavanah, Sarah; Lewis, Seth C.
Cell-phone-only (CPO) households differ along key variables from non-CPO households, creating potential coverage biases in landline-only random-digit-dialing (RDD) surveys. Researchers have attempted to correct for this by weighting their data based on demographic differences. Previous research, however, has not examined CPO coverage biases in media-use surveys—an important oversight as cell phone use is itself a media choice. This article presents a secondary analysis of Pew's 2012 media consumption survey and concludes that demographics alone are not adequate controls for the CPO bias in media-use surveys.